2000
DOI: 10.1024/1023-9332.6.4.169
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Value of Interleukin-6 and C-Reactive Protein in Acute Appendicitis

Abstract: The aim of this study is prospectively to evaluate the serum C-reactive protein (CRP) and interleukin-6 (IL-6) levels in detection of acute appendicitis in patients with right iliac fossa pain. Data were collected in prospective manner on 102 consecutive patients with right iliac fossa pain. Laparotomy was performed for suspected acute appendicitis for 55 of the 102 patients, of whom 49 patients had appendicitis, 6 patients non-appendicitis (NA), and the other 47 patients had nonspecific abdominal pain (NSAP) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
28
0
1

Year Published

2004
2004
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(33 citation statements)
references
References 0 publications
4
28
0
1
Order By: Relevance
“…Many studies have confirmed accuracy and effectiveness of these tests. [14][15][16] Nevertheless, none of these tests is sufficient or suitably specific to decrease negative appendectomy rate by itself.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have confirmed accuracy and effectiveness of these tests. [14][15][16] Nevertheless, none of these tests is sufficient or suitably specific to decrease negative appendectomy rate by itself.…”
Section: Discussionmentioning
confidence: 99%
“…[4][5][6] Some groups have reported more specific findings: raised CRP values have been shown to correlate with complications such as perforation or appendix abscess. [7][8][9] These studies have, however, all been retrospective, focusing on blood tests done on patients who have had appendicectomy. More limited data are available from prospective analyses in patients presenting with right iliac fossa pain.…”
mentioning
confidence: 99%
“…9 Though novel inflammatory markers including interleukin-6 have been assessed with little additional merit, [10][11][12] the most commonly used are total white cell count (WCC), neutrophil count (NC) and C-reactive protein (CRP).…”
mentioning
confidence: 99%